Levosimendan, milrinone, and dobutamine in experimental acute pulmonary embolism - Mads D. Lyhne (Pulmonary Circulation, 2021)
Acute pulmonary embolism is a frequent condition in emergency medicine and potentially fatal. Cause of death is right ventricular failure due to increased right ventricular afterload from both pulmonary vascular obstruction and vasoconstriction. Inodilators are interesting drugs of choice as they may improve right ventricular function and lower its afterload. We aimed to investigate the cardiovascular effects of three clinically relevant inodilators: levosimendan, milrinone, and dobutamine in acute pulmonary embolism. We conducted a randomized, blinded, animal study using 18 female pigs. Animals received large autologous pulmonary embolism until doubling of baseline mean pulmonary arterial pressure and were randomized to increasing doses of each inodilator. Effects were evaluated with bi-ventricular pressure–volume loop recordings, right heart catheterization, and blood gas analyses. Induction of pulmonary embolism increased right ventricular afterload and pulmonary pressure ( p  < 0.05) causing right ventricular dysfunction. Levosimendan and milrinone showed beneficial hemodynamic profiles by lowering right ventricular pressures and volume ( p  < 0.001) and improved right ventricular function and cardiac output ( p  < 0.05) without increasing right ventricular mechanical work. Dobutamine increased right ventricular pressure and function ( p  < 0.01) but at a cost of increased mechanical work at the highest doses, showing an adverse hemodynamic profile. In a porcine model of acute pulmonary embolism, levosimendan and milrinone reduced right ventricular afterload and improved right ventricular function, whereas dobutamine at higher doses increased right ventricular afterload and right ventricular mechanical work. The study motivates clinical testing of inodilators in patients with acute pulmonary embolism and right ventricular dysfunction.